Development of the good food planning tool: A food system approach to food security in indigenous Australian remote communities. (July 2015) - Brimblecombe, Julie; van den Boogaard, Christel; Wood, Beverley; Liberato, Selma C; Brown, Jacqui; Barnes, Adam; Rogers, Alison; Coveney, John; Ritchie, Jan; Bailie, Ross
Abstract: Few frameworks exist to assist food system planning, especially for Indigenous Australian remote communities. We developed a Good Food Planning Tool to support stakeholders to collectively plan and take action for local food system improvement. Development occurred over a four-year period through an evolving four phase participatory process that included literature review, several meetings with representatives of various organisations and communities and application of the Tool with multi-sector groups in each of four Indigenous Australian remote communities. A diverse range of 148 stakeholders, 78 of whom were Indigenous, had input to its development. Five food system domains: (i) Leadership and partnerships; (ii) Traditional food and local food production; (iii) Food businesses; (iv) Buildings, public places and transport; (v) Community and services and 28 activity areas form the framework of the Tool. The Good Food Planning Tool provides a useful framework to facilitate collective appraisal of the food system and to identify opportunities for food system improvement in Indigenous Australian remote communities, with potential for adaptation for wider application. Highlights: The GFPT was user-friendly and suitable for use in four contextually different remote communities. There were consistencies between activity areas identified by Indigenous stakeholders and those identified through best available evidence and other expert opinions. The GFPT offers a process to enable incremental improvement in the local food system through: − Connecting stakeholders and shaping their thinking and actions through facilitated dialogue − Harnessing the unique assets and capacities of communities − Bringing the experiences, knowledge and views of Indigenous and non-Indigenous stakeholders together Further research is required on the outcomes of the GFPT process on local food system quality in the long-term.